COLOR BLIND DETECTION APPLICATION DESIGN USING THE ISHIHARA METHOD USING THE ANDROID OS PLATFORM - Andika Bayu Hasta Yanto; Ahmad Fauzi; Andry Maulana; Rifky Permana; Dwi Yuni Utami (INFOKUM, 2022)
Not all people know that some of them have eye abnormalities, one of which is color blindness, even though they can see the dominant color, but there are several colors that they cannot see, therefore color blind people on average are not aware of their good vision they feel now because in testing color blindness someone has to discuss and do some testing and usually people will do a color blind test.In response to this, with the application for detecting color blindness based on Android, the community carries out independent tests using the Ishihara method regarding the identification of color blindness so that if someone does have an eye disorder, they can immediately consult a specialist doctor regarding the actions and treatment that must be carried out in order to resolve the problem